He death of myths or a crisis of imagination? “Mythical thinking”, the phantasms of imagination, and a few remarks on Olga Tokarczuk’s works - Jasionowicz, Stanisław (Prace Polonistyczne, 2023)
The aim of the article is to examine the status of myths in contemporary literature and in reflections on postmodernity. In the first part, Jasionowicz raises questions about the ontological and cognitive status of myth in literature and cultural studies. Although the very concept of myth remains controversial, he recognizes it as a source of “rich narratives”, rooted in the archetypal potential of the creative imagination and capable of having a long-lasting, cultural, intersubjective “life.” There are also narratives that are less durable, as they attempt to detach themselves from their anthropological foundations. Olga Tokarczuk’s works serve as examples of processes that can be considered manifestations of the “non-binary imagination” visible in world literature of the first decades of the twentyfirst century. On the discursive (ideological) level, Tokarczuk’s vision of the world and the interrelated concepts are extremely dichotomous, which relates to the “interventionist” character of most of her texts. However, on the imaginative level, her imagination is non-dichotomous (intimist); it is a type of imagination that Gilbert Durand described as belonging to “mystical structures.” The lack of imaginative coherence between the ideologemes of critical postmodernism (built on the rhetoric of a radical gender conflict or the insurmountable “us-them” opposition) and the mycelial imagination has yet to consider such ideas and discourses as a new form of myth. Perhaps they could become myths if only they were able to create productive tension between these two systems of imagination and thus generate new meanings.